Contributions of the Cherenkov Telescope Array (CTA) to the 6th International Symposium on High-Energy Gamma-Ray Astronomy (Gamma 2016) - CTA Consortium, The; Abchiche, A.; Abeysekara, U.; Abril, Ó.; Acero, F.; Acharya, B. S.; Adams, C.; Agnetta, G.; Aharonian, F.; Akhperjanian, A.; Albert, A.; et al. (2016)
List of contributions from the Cherenkov Telescope Array (CTA) Consortium presented at the 6th International Symposium on High-Energy Gamma-Ray Astronomy (Gamma 2016), July 11-15, 2016, in Heidelberg, Germany.
Keywords: Astrophysics - High Energy Astrophysical Phenomena